Access to Health Service Related to Use of Antenatal Care Facilities at the Kawangu Health Centre, East Sumba - Nara Adriana; Luh Putu Lila Wulandari; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: The study aims to determine factors influencing the utilization of accredited government-run ANC facilities at the Kawangu Health Centre. Methods: Research was a cross-sectional study, with a total of 85 samples taken by consecutive sampling from the Kawangu Health Centre. The dependent variable was the use government-run ANC facility at the Kawangu Health Centre. The independent variables were knowledge, awareness, attitudes, access to health services, frequency of receiving information and family support. The data were collected by interview using questionnaires. The data analysis includes univariate, bivariate (chi-square) and multivariate analysis with logistic regression. Results: The results of the study indicated that there was a significant relationship between the use of accredited government-run ANC facilities with maternal knowledge/awareness (p=0.001), attitude (p<0.001), ability to access to health services (p<0.001), frequency of information (p=0.039), and family support (p<0.001). Multivariate analysis indicated that the only significant independent variable related to the use of adequate delivery was the ability to access health services with OR =11.68 (95%CI: 1.37 to 99.89). Conclusion: An inability to access either due to distance to travel, lack of vehicle and/or infrastructure concerns such as poor quality/lack of roads was the dominant variable in the utilization of accredited government-run ANC facility.